2012
DOI: 10.5177/ntvt.2012.10.12210
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis: review of types, aetiology, diagnostics, and treatment 1

Abstract: A scoliosis is a flexible or rigid deformity of the spine in the frontal plane. There are several types of scoliosis, each with specific characteristics. The most prevalent types are idiopathic, congenital, and neuromuscular scoliosis and scoliosis in adults. The aetiology is varied and largely undetermined. Essential components of diagnostics are patient history, physical examination, and radiographs. Treatment options are a conservative approach involving observation and follow-up, a conservative approach in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Scoliosis has been observed in 0.5% to 2% of the population (20-23). Our study showed that the prevalence of scoliosis could be much higher in WBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis has been observed in 0.5% to 2% of the population (20-23). Our study showed that the prevalence of scoliosis could be much higher in WBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular scoliosis is usually formed at a young age, but may also develop in adulthood. Its characteristic feature is a rapidly progressive curvature of the spine [2].…”
Section: Discussionmentioning
confidence: 99%
“…Family history is a risk factor and recent genetic advances identify several candidate loci for idiopathic scoliosis, particularly the LBX1 region as a prime susceptibility locus [5]. Congenital scoliosis is defined as a lateral spinal deformity caused during embryonic vertebral development and affects approximately 1 per 1,000 live births [6,7]. The etiology of congenital scoliosis is largely unknown and is attributed to genetic and environmental factors [8].…”
Section: Introductionmentioning
confidence: 99%